The use of ultrasonic densitometry in assessing bone mineral density and determining the 10-year risk of osteoporotic fractures in older women in the family doctor practice - Lukianets, Yevheniia (ScienceRise: Medical Science, 2021)
Osteoporosis is the fourth most common disease after cardiovascular, cancer and endocrine diseases. With an increase in life expectancy, it becomes one of the main causes of deterioration in health and an increase in mortality. The aim of the study. To identify women with low bone density using ultrasound densitometry and assess the risk of osteoporotic fractures. Materials and methods. The study was based on a survey of 31 women in the Odessa region, the average age of the subjects was 57±9.1 years, the average body weight was 75.74±12.5 kg, height 162.8±0.1 cm, the average BMI was 28.57±4.5. All women were divided into groups by age with a ten-year interval and by densitometry indices. Results. Decrease in bone density was found in 51.6 % of examined women. The lowest BMD was in the age group of 70–79 years, and the largest numbers of respondents with osteopenic changes were at the age of 50–59. A linear correlation was found between BMD and age at the level of significance p=0.007. The linear regression equation is: t=-0.03968 *age+1.268, (r=-0.473). In women with osteopenia, a significant increase in indicators was found for almost all algorithms for assessing the 10-year risk of fractures at p<0.05 (except for FRAX Hiр without BMD (p=0.087)) and a significant decrease in ultrasound densitometry indicators compared with women with normal BMD. Women with fractures had significantly higher scores according to the FRAX Total algorithms without BMD (p=0.002), FRAX Hiр without BMD (p=0.004) and Q-fracture Hiр (p=0.044). Conclusions. Most women had osteopenic manifestations according to ultrasound densitometry. Age significantly correlates with BMD parameters. The numbers of women with changes in the structure of bone tissue increases with age, and, after 70 years, all women have osteopenic manifestations. The algorithms for assessing the 10-year risk of fractures FRAX and Q-Fracture reliably correlate with densitometry indicators. The combination of ultrasound densitometry with algorithms for assessing the risk of osteoporotic fractures significantly increases the diagnosis of osteoporosis